Detection of delaminations in AS4/PEEK composite plates using highly nonlinear solitary waves. (1st June 2022) - Yoon, Sangyoung; Kim, Guenil; Schiffer, Andreas; Cantwell, Wesley J.; Kim, Eunho; Kim, Tae-Yeon
Abstract: We experimentally investigate a non-destructive evaluation (NDE) technique to detect defects in an AS4/PEEK fiber-reinforced thermoplastic composite using highly nonlinear solitary waves (HNSWs). HNSWs are generated using an experimental setup of a granular crystal sensor composed of a one-dimensional chain of steel beads. The granular chain is vertically aligned and placed in contact with the surface of the laminated composites containing a defect through the depth of their thickness. The influence of the defect and the defect location in AS4/PEEK is examined by analysing the characteristics (i.e., delay and amplitude) of the reflected HNSWs. Experimental results demonstrate the capability of the proposed HNSW-based NDE scheme in identifying defects in AS4/PEEK laminated composites, offering a low-cost and robust alternative to existing NDE methods.